Modified Incision For Orbicularis Oris Function Conservation In Intra Oral Lesions - Dr. Mira Sen; Dr. Asit Ranjan Dasgupta; Dr. Meera Chatterjee; Dr. Dipankar Chatterjee; Dr. N. Vani; Dr. Amit Bhowmik (Indian Journal of Plastic Surgery, 1992)
A new incision with a view to reduce vascular compromise, to have a better control of saliva, speech and mastication, in oral cancer surgery is described.